If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(4x + -7) = 5x + -1x + 21 Reorder the terms: x + -1(-7 + 4x) = 5x + -1x + 21 x + (-7 * -1 + 4x * -1) = 5x + -1x + 21 x + (7 + -4x) = 5x + -1x + 21 Reorder the terms: 7 + x + -4x = 5x + -1x + 21 Combine like terms: x + -4x = -3x 7 + -3x = 5x + -1x + 21 Reorder the terms: 7 + -3x = 21 + 5x + -1x Combine like terms: 5x + -1x = 4x 7 + -3x = 21 + 4x Solving 7 + -3x = 21 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + -3x + -4x = 21 + 4x + -4x Combine like terms: -3x + -4x = -7x 7 + -7x = 21 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + -7x = 21 + 0 7 + -7x = 21 Add '-7' to each side of the equation. 7 + -7 + -7x = 21 + -7 Combine like terms: 7 + -7 = 0 0 + -7x = 21 + -7 -7x = 21 + -7 Combine like terms: 21 + -7 = 14 -7x = 14 Divide each side by '-7'. x = -2 Simplifying x = -2
| 2x+9-6W=-19 | | -4.2+31.5=-65.1x | | -15000000x+3056890000=5550000x+2085000000 | | p-(23)=11 | | -8=2/x | | 36a-9= | | 10k=2 | | 8x+7(3x+-20)=-24 | | z-12=5z+2 | | (-3)-g=(-3) | | (3x+45)=60 | | f(x)=-7 | | 2x/5=3/x | | 2m+4=5m+6 | | 8x+7(3x+-20)=16 | | X=2.7 | | 13-2(4x-2)=3(-2x-1)+8x | | 7x+4y=40 | | 3x+4y=-32 | | (4x-90)=90 | | 10.4-1.5x=3.6x-40.4+10 | | 4n=-17 | | 0.3x+24*5x*0.2x-15= | | 2y+3=3(2)-7 | | 6x-10=158 | | n+6=8*7 | | (0.35)(s+0.34)+(0.15s)=(0.2s-1.66) | | 9(b+1)=3b+15 | | 3g+2(-7+3g)=1-g | | (3x+5y)-(4x+11)=0 | | 17y-5x=46 | | .14(14+3.5)-3q=9 |